PEMBUATAN BIOGAS DARI LIMBAH BHO PENYAMAKAN KULIT DENGAN STARTER EFFLUENT DIGESTER AKTIF DAN CO-DIGESTION DENGAN KOTORAN SAPI - Swatika Juhana; Prasetyo Hermawan; Wahyu Fajar Winata; Arini Wresta; Ika Yanti (Politeknik ATK Yogyakarta, 2020)
ABSTRACT This research aims to utilize BHO tannery liquid waste for biogas production and to examine the effect of active digester effluent on the co-digestion of biogas production by co-digestion of BHO liquid waste and cow manure. The experiment began with an analysis of the character of the leather tanning BHO liquid waste. The biogas production is carried out in batches in an anaerobic biogas digester. The experiment was started by entering raw materials for BHO liquid waste: cow dung: active digester effluent with a ratio of D1 = 4: 2: 0; D2 = 4: 0: 2; D3 = 6: 0: 0. Observation of the addition of gas was carried out by means of a manometer to measure the increase in gas pressure produced in the digester every day until the 15th day. The results of the analysis of BHO wastewater showed high BOD and COD levels, namely 3265 mg / L and 11231.2 mg / L. The results of making biogas show increased gas pressure (gas formation) in digester D1 and D2. The result of D1 (BHO waste without starter) gas production is a lot at the beginning and then decreases. In D2 (BHO waste with the addition of starter and cow dung), it shows that gas production is formed on the 8th day with constant pressure until the 15th day and is still producing. In the D3 digester (BHO liquid waste without a starter and cow dung) no gas is formed.